Spectral mode surface plasmon spectroscopy for surface mechanics characterization - Wong, Chee Cheong. (2009)
This project proposes to use a spectral SPR (surface plasmon resonance spectrometer) equipped with an environmental chamber and a temperature-regulated sample stage to study the thermal desorption of SAMs (self-assembled monolayers) on Au surfaces. The equipment was designed and assembled in-house using off the shelf optical and electro-mechanical components. Using dodecanethiol and standard Au surfaces, the system has been calibrated with respect to simulated data of the expected phenomenon of SPR. After a thorough investigation of how surface preparation on various Au surfaces (pulsed laser deposited, sputtered, and electron-beam evaporated) affect the structural quality of SAMs (as determined by contact angle measurements), we have been to able to provide the reference standards for a thermal desorption study using SPR. The point of the characterization is to determine, via thermal SPR, at which temperature a particular SAMs group would desorb from a specific Au surface. This data has been collected and compared with literature with good agreement. Based on this, we are able to deduce the temperature at which SAMs may be desorbed from a similar Au surface used in a thermocompression bonding experiment, in which we have demonstrated that Au joints with comparable strength and electrical conductivity can be produced with lower temperature and pressure requirements when the Au surfaces are previously with a SAMs layer. We have attributed this bonding improvement to the passivation of Au surfaces, with a remaining question of what happens to the SAM layer when the metallurgical bonding has been accomplished.